Detecting income smoothing behaviour of Turkish listed companies through empirical tests using accounting changes - Atik, Asuman (My University, 2005)
Company managers have flexibility when selecting accounting methods that help to provide relevant, reliable and timely information about assets, liabilities, future cash flows, the real performance of their company. Sometimes this flexibility motivates managers to choose accounting methods or to change employed accounting methods in order to increase, decrease or smooth income figures. Objective of this thesis is to detect income smoothing behaviours of Turkish listed firms through empirical tests using discretionary accounting changes. Parallel to Moses' (1987) study, income smoothing is accepted a motivation of discretionary accounting changes (DACs). The sample of the study is composed of the firms listed on ISE between 1998-2003 and made discretionary accounting changes. Using the smoothing behaviour index of Moses (1987), the sample firms are classified as smoothers and non-smoothers, and nearly 60 percent of the sample firms are smoothers and 40 percent of the firms are non-smoothers. Furthermore, relationship between smoothing behaviour and firm size, employee costs, ownership structure, industry, debt ratio, prechange earnings deviation and directional impact of the change is also analysed. Most of the discretionary accounting changes were made in 1999 and 2001 that were the two big economical crises years. Managers who could not attain the expected earnings level with natural operations in those hard periods might have selected to arrange income figure with discretionary accounting changes. Analyses also show that the monetary effects of the discretionary accounting changes generally helped to decrease prechange earnings when they are higher than zero and to decrease losses of the firms. In conclusion, income smoothing, the economical characteristics of the periods in which the discretionary accounting changes are made and the desire to have a net income close to zero are the possible motivations of the discretionary accounting changes.

Yöneticiler mali tablo kullanıcılarına sunulacak bilgilerin hazırlanmasında ve sunulmasında kullanacakları muhasebe metotlarını belirli sınırlar dahilinde serbestçe seçebilme esnekliğine sahiptirler. Asıl amaçları işletmenin varlıkları, borçları, gelecekteki nakit akışları, gerçek performansı hakkında, karar vericilerin kararlarıyla ilgili, zamanlı ve güvenilir bilgiler sunmaktır. Fakat bu esneklik yöneticilere kârlarının tutarını arttıran, azaltan veya düzleştiren muhasebe metotlarını seçme veya kullanmakta oldukları metotları değiştirme seçeneği de sunmaktadır. Bu tezin amacı İMKB firmalarının kâr düzleştirme davranışlarını isteğe bağlı muhasebe değişikliklerinin kullanıldığı ampirik testler vasıtasıyla saptamaktır. Moses'in (1987) çalışmasına paralel olarak, bu tezde de kâr düzleştirme isteğe bağlı muhasebe değişikliklerini motive eden bir faktör olarak kabul edilmiştir. Örnek kütleyi oluşturan 1998-2003 yılları arasında muhasebe değişikliği yapan İMKB firmaları, Moses'in (1987) kâr düzleştirme endeksi kullanılarak, kâr düzleştiren ve kâr düzleştirmeyen olarak sınıflandırılmışlardır. Firmaların yaklaşık % 60'ı kâr düzleştiren, % 40'ı ise kâr düzleştirmeyen firmalardır. Ayrıca firma büyüklüğü, işçi maliyetleri sahiplik yapısı, endüstri, toplam borç / toplam varlık oranı, muhasebe değişikliği öncesi kârın beklenen kârdan sapma miktarı ve muhasebe değişikliğinin etkisi gibi değişkenler ile kâr düzleştirme davranışı arasındaki ilişki incelenmiştir. Çoğu isteğe bağlı muhasebe değişikliğinin iki büyük ekonomik krizin yaşandığı 1999 ve 2001 yıllarında yapıldığı görülmüştür. Ekonomik açıdan zor koşullarda doğal faaliyetleri ile hedefledikleri kâr rakamına ulaşamayan yöneticilerin isteğe bağlı muhasebe değişiklikleri yoluyla kâr rakamını ayarlamayı seçmiş olabileceği kanaatine varılmıştır. Analizler muhasebe değişikliklerinin parasal etkilerinin genellikle değişiklik öncesi kârı veya zararı azaltıcı yönde olduğunu da göstermektedir. Sonuç olarak, kâr düzleştirme, isteğe bağlı muhasebe değişikliğinin yapıldığı dönemin koşulları ve sıfıra yakın bir net kâr rakamına sahip olma isteği muhasebe değişikliklerini motive eden muhtemel etmenlerdir.
Keywords: Muhasebe; Yönetim ve yardımcı hizmetler